Experimental verification of the effectiveness of implementing a differentiated approach in training future physical education teachers - Vlasiuk, Roman (Journal of Education, Health and Sport, 2023)
The effective training of future specialists in physical culture and sports necessitates a comprehensive system of specialized knowledge, which forms a crucial part of a teacher's competence. This research aims to enhance the theoretical training level of students enrolled in the Faculty of Physical Education. The experiment involved 36 first-year students from TNPU. Initially, the collected data revealed an average score of 55% across all sections of theoretical training, indicating a low level of knowledge. However, after the experiment, significant improvements were observed in the areas of general development (4.22±0.12), drill exercises (4.11±0.10), injury prevention in gymnastics classes (4.17±0.12), and gymnastics in the system of physical education of Ukraine (4.03±0.15).